Sosialisasi Pemanfaatan Limbah Tempe Sebagai Pupuk Organik Cair untuk Pengelolaan Berkelanjutan di Desa Kuripan Kertoharjo - Pipin Supinah; Wahyu Fajar Setiawan; Setyardi Pratika Mulya (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Tempe is a fermented soybean product commonly consumed by people in Indonesia. The presence of tempe industry is often found, especially in the village of Kuripan Kertoharjo. In addition to being a pillar of the people's economy, it also creates its own problems. Processing soybeans into tempeh will produce a byproduct in the form of tempe liquid waste which has the potential to disrupt environmental harmony. The negative impact of tempe waste can be minimized by being used as liquid organic fertilizer. The purpose of this program is that the community can process tempe waste into liquid organic fertilizer so that it can reduce tempe waste that is discarded and is beneficial to the community. The method used before the program is by observing the number of tempe industries that will be used as samples. Tempe waste samples were used from five different tempe industrial sites. The method used in the program is socialization with lecture techniques and simple practices using tempe waste and EM4 as compost activators. The result of this program is the program is divided into two activities, namely socialization and practice, where the socialization consists of the delivery of material related to the environment, waste, and liquid organic fertilizer. Simple practice is done by practicing how to make liquid organic fertilizer in front of the community then followed by the community. Every activity of the program runs smoothly and it is hoped that the utilization of tempe waste can be carried out continuously to prevent environmental pollution. Keywords: EM4, liquid organic fertilizer, tempe industry, tempe waste